Role of immunotherapy in the overall survival of gastrointestinal cancer patients with liver metastases - Taoyuan M Beninato; Saber A Amin; Michael J Baine; Chi Lin (Hepatic Oncology)
Aim: To investigate the role of immunotherapy in the overall survival (OS) of gastrointestinal cancer patients who have liver metastases at the time of the primary site cancer diagnosis.Materials & methods: Survival outcome was compared between groups with immunotherapy and groups without immunotherapy.Results: Chemoimmunotherapy was associated with improved OS (hazard ratio [HR] 0.768; 95% CI 0.739–0.800; p < 0.001) compared with chemotherapy alone. Radiotherapy to the primary site plus chemoimmunotherapy was also associated with improved OS (HR 0.796; 95% CI 0.705–0.898; p < 0.001) compared to chemoradiation. Chemoimmunotherapy with radiotherapy to metastatic sites (except liver) was associated with improved OS (HR 0.771; 95% CI 0.706–0.842; p < 0.001) compared to chemoradiation.Conclusion: Immunotherapy plus chemotherapy or chemoradiation was associated with improved OS compared with chemotherapy or chemoradiation without immunotherapy.